Palliative care research centre's move into social media: constructing a framework for ethical research, a consensus paper. Issue 2 (28th January 2016) - Hopewell-Kelly, Noreen; Baillie, Jessica; Sivell, Stephanie; Harrop, Emily; Bowyer, Anna; Taylor, Sophia; Thomas, Kristen; Newman, Alisha; Prout, Hayley; Byrne, Anthony; Taubert, Mark; Nelson, Annmarie
Abstract : Background: Social media (SM) have altered the way we live and, for many, the way we die. The information available on even the rarest conditions is vast. Free from restrictions of mobility, time and distance, SM provides a space for people to share experiences of illness, death and dying, and potentially benefit from the emotional and practical support of others n similar positions. The communications that take place in these spaces also create large amounts of 'data' which, for any research centre, cannot be ignored. However, for a palliative care research centre the use of this 'data' comes with specific ethical dilemmas. Methods: This paper details the process that we, as a research, went through in constructing a set of ethical guidelines by which to work. This involved conducting two consensus days; one with researchers from within the centre, and one with the inclusion of external researchers with a specific interest in SM. Results: The primary themes that emerged from the consensus meetings includes; SM as a public or private space; the status of open and closed groups; the use of historical data; recruiting participants and obtaining informed consent and problems of anonymity associated with dissemination. Conclusions: These are the themes that this paper will focus on prior to setting out the guidelines that we subsequently constructed.